THE DOMINANT ID OF THE CHARACTER STAPLETON AS PORTRAYED IN THE NOVEL “THE HOUND OF THE BASKERVILLES” BY SIR ARTHUR CONAN DOYLE - Lesmana, Allan Budi; Afriana, Afriana (SCIENTIA JOURNAL, 2019)
This research is an application of Freud’s psychoanalysis theory into the novel “The Hound of the Baskervilles” by Sir Arthur Conan Doyle. The aim of the research is to find out the dominant id of the antagonist character named Stapleton and to reveal the cause of this character in threatening the Baskervilles family. The researcher uses psychological approach by Sigmund Freud or the theory of id, ego and superego. The researcher analyses and gives explanation about the dominant id of Stapleton character and reveals the motif of the character in threatening the Baskervilles. The researcher conducts a qualitative research. The data are obtained in the form of quotations from the novel “The Hound of the Baskervilles” by Sir Arthur Conan Doyle. The method of collecting data used is document study. The researcher uses content analysis as the method of analyzing data. The data are presented qualitatively and descriptively. The finding of the research shows that the id of Stapleton character is dominant because everything that Stapleton had done was only to fulfil his bad desire, his terrible wish captured the evidence that the id of this character was dominant and the motif of this character in threatening the Baskervilles is to obtain the riches and valuable estate of the Baskervilles.